The regulation of synthesis and properties of the protein product of open reading frame P of the herpes simplex virus 1 genome. - Lagunoff, M (1995)
Open reading frame P (ORF P) maps in the inverted repeat sequence ab and b'a' flanking the long unique (UL) sequence of the herpes simplex virus 1 genome, within the sequence reported to be transcribed during latent infection of sensory neurons. Both the protein and the RNA were previously reported to be expressed only in cells infected with a deletion mutant or with a mutant carrying a ts lesion in the alpha 4 gene encoding the infected cell protein no. 4 (ICP4), a major regulatory protein of the virus. In this report we show that (i) disruption of the ICP4 DNA binding site by replacement mutagenesis resulted in the overexpression of ORF P protein even at permissive temperatures, leading to productive infection; (ii) the expression of ORF P does not require prior viral protein synthesis; (iii) late in infection the ORF protein P is processed into multiple forms characterized by a slower electrophoretic mobility in denaturing gels; (iv) ORF P protein accumulates in nuclei of infected cells; and (v) in some nuclei of infected cells, ORF P protein is organized in the form of rods traversing the nucleus from the basolateral to the apical side. We conclude that ORF P has many of the properties predictive of a viral gene group, which we designate pre-alpha. Specifically, these could be induced by the alpha transinducing factor (also known as VP16) carried in the virion; they would be firmly shut off by the onset of expression of alpha genes required for productive infection; and in the absence of repressive effects of ICP4, their expression could be dependent on the number of viral DNA copies available for transcription. Finally, the productively infected cell would evolve a way of disposing excess pre-alpha proteins by posttranslational processing.